HISTORICAL SPECIAL INTEREST TOURISM: THE EVOLUTION OF MOUNTAINEERING IN SOUTH AFRICA - Christian M. ROGERSON; Jayne M. ROGERSON (Revista Română de Geografie Politică)
Scholarship on special interest tourism has burgeoned since the 1980s. Although this expanding research interest is relatively new, the phenomenon of special interest tourism is not of recent origin as many of its forms, such as mountaineering, exhibit a long historical record. Most research on special interest tourism concentrates on contemporary issues. The objective is to present a historical perspective on special interest tourism. Using archival sources an analysis is undertaken of the evolution of mountaineering in South Africa as a recreational sport and incipient form of special interest tourism. Cape Town’s Table Mountain and the Drakensberg mountains provide the geographical focus of discussion. The results demonstrate that during the 1920s and 1930s tourism promoters in South Africa acknowledged the potential of special interest mountaineers to contribute to tourism growth. The documented experience of early mountaineering in South Africa provides an example of racism in recreation by showing that the country’s recreational practices became constructed around politicallyimposed racial hierarchies.